Dampak Berganda (Multiplier Effect) Objek Wisata Terhadap Perekonomian Masyarakat Lokal - Nurul Pajriah, Putri; Sulaksana, Jaka; Umyati, Sri (Universitas Garut, 2025)
Tourism is one of the development sectors currently being promoted by both central and local governments. This study aims to analyze the multiplier effect of tourism activities at the Situ Cipanten tourist site on the local economy of Gunungkuning Village, Sindang Subdistrict, Majalengka Regency. The research adopts a mixed methods approach involving 158 respondents, consisting of 99 tourists, 41 workers, and 18 MSME actors selected through stratified sampling. Data were collected through questionnaires, interviews, observations, and documentation, and analyzed using the multiplier effect approach. The results indicate that tourism at Situ Cipanten has a significant economic impact, with a Keynesian Income Multiplier of 0.2, a Type I Income Multiplier of 2.4, and a Type II Income Multiplier of 3.2. These effects are reflected in the emergence of new businesses, increased demand for local raw materials, and higher household consumption. The study concludes that the development of tourism at Situ Cipanten contributes positively to sustainable local economic growth.